2019
DOI: 10.3389/fimmu.2019.01035
|View full text |Cite
|
Sign up to set email alerts
|

The Epitope-Specific Anti-human CD4 Antibody MAX.16H5 and Its Role in Immune Tolerance

Abstract: T cell modulation in the clinical background of autoimmune diseases or allogeneic cell and organ transplantations with concurrent preservation of their natural immunological functions (e.g., pathogen defense) is the major obstacle in immunology. An anti-human CD4 antibody (MAX.16H5) was applied intravenously in clinical trials for the treatment of autoimmune diseases (e.g., rheumatoid arthritis) and acute late-onset rejection after transplantation of a renal allograft. The response rates were remarkable and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…After a minimum of 4 hours of recovery time, 2 × 10 5 or 4 × 10 5 CD34 + HSC were injected intrahepatically. The transplantation of PBMC was carried out by intravenous injection of 2 × 10 7 cells (preincubated with or without anti-human CD4 antibody MAX.16H5 IgG 4 to suppress the graft-vs-host reaction potentially mediated by the graft, a concept which we already described earlier 4,13,14 ). PB samples were obtained by retrobulbar bleeding under anesthesia.…”
Section: Humanization Of Nsg Micementioning
confidence: 99%
“…After a minimum of 4 hours of recovery time, 2 × 10 5 or 4 × 10 5 CD34 + HSC were injected intrahepatically. The transplantation of PBMC was carried out by intravenous injection of 2 × 10 7 cells (preincubated with or without anti-human CD4 antibody MAX.16H5 IgG 4 to suppress the graft-vs-host reaction potentially mediated by the graft, a concept which we already described earlier 4,13,14 ). PB samples were obtained by retrobulbar bleeding under anesthesia.…”
Section: Humanization Of Nsg Micementioning
confidence: 99%
“… 60 , 61 , 62 Similar to the mAb cocktail used in the current study, these drugs clear host T cells and may be effective in our HSCT gene therapy protocol. Alternatively, investigational mAbs that specifically target CD4 (e.g., MAX.16H5 63 , 64 or IT1208 65 ) or CD3 66 (e.g., teplizumab, otelixizumab, visilizumab, or foralumab) might be considered. A similar approach to that taken in a recent phase 1/2 clinical trial of HSC-directed LV gene therapy for the primary immunodeficiency Wiskott-Aldrich syndrome, in which fludarabine and rituximab (CD20 mAb) were used to achieve immune cell depletion prior to transplantation, could be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the regulation of donor-derived CD4 + T cells and the production of some critical cytokines (such as IFN- γ ) could affect the development of aGVHD [ 5 ]. CD4 + T cells have been studied as the potential treatment targets for GVHD in a large number of clinical trials [ 4 , 6 ]. A clinical study, however, found that peripheral blood stem cell (PBSC) graft containing more mature T cells did not increase the incidence and severity of aGVHD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%